Consonant acquisition: a first approach to the distribution of errors in four positions in the word - Llac, Silvia; Palmada, Blanca (Revista de Investigación en Logopedia, 2012)
The goal of this study is to describe the behavior of errors in two types of onsets (initial and intervocalic) and two types of codas (in the middle and end of the word) in order to determine if any of these positions are more prone to specific types of errors than the others.We have looked into the errors that are frequently produced in these four contexts during the acquisition of consonant sounds in the Catalan language. The data were taken from a study on the acquisition of consonants in Catalan, carried out on 90 children between the ages of 3 and 5 years from several kindergarten schools. The results do show that there are characteristic errors depending on the position within the word.
Keywords: Catalan language; Consonant errors; Language acquisition; Phonology.